IMPACT OF CLEAN WATER INFRASTRUCTURE TO INCOME INEQUALITY, WITH ECONOMIC GROWTH AS INTERVENING - Sakti Prabowo; Mohamad Choirul Rijal Makrufan (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
The purpose of this study is to examine the relationship between clean water infrastructure development and income inequality. From a panel dataset year 2011 to 2018, this study uses clean water infrastructure development, Economic growth, and path analysis as independent variables to observe the effect on income equality. Statistically, clean water infrastructure development does not affect income inequality, directly nor indirectly. Economic growth does not affect income inequality. The insignificant result may be caused by the short length of time. The results of this study do not intend to suggest policymakers reduce clean water infrastructure development. Policymakers should apply a distribution policy by considering the needs and potential of the community to make the development more valuable.